Les connecteurs discursifs comme moyen de produire un effet humoristique dans « La vie devant soi » de Romain Gary et sa traduction en polonais – étude traductologique - Szeflińska-Baran, Magdalena (Studia Romanica Posnaniensia, 2013)
The subject of the paper is linguistic humour examined from the point of view of its functioning in intralinguistic literary communication (monolingual) as well as from a much broader point of view which comprises the problem of crosslinguistic and crosscultural transfer of facetious elements. The analysis has as its subject different forms of verbal humour which can be observed in linguistic communication that is understood as any manifestation of linguistic activity. Having assumed such a broad perspective of communication allowed to analyse humour from the point of view of its functioning, not only within one cultural-linguistic community, but also to analyse this phenomenon in the crosslinguistic and crosscultural context.